2023
DOI: 10.5530/ijper.55.1s.62
|View full text |Cite
|
Sign up to set email alerts
|

Smart UV Derivative Spectrophotometric Methods for Simultaneous Determination of Metformin and Remogliflozin: Development, Validation and Application to the Formulation

Abstract: Background:The result of pharmaceutical industry research for the new class and the new combination of drugs for the treatments of diabetes is the newly approved combination of metformin (MET) and remogliflozin (REM). For the quality control of this formulation, three smart, reproducible and non-sophisticated spectroscopic techniques were developed by modification of UV spectra. Materials and Methods: The first two methods were based on the measurements of the peak height of the third derivative and second der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The literature survey found that for this triple drug formulation, no forced degradation study was performed. [4][5][6][7][8][9][10][11][12][13][14] So, the present research aimed to develop a stability indicating reverse phase liquid chromatographic method for the simultaneous determination of MET, VIL and REM in bulk and drug formulation suitable for routine analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey found that for this triple drug formulation, no forced degradation study was performed. [4][5][6][7][8][9][10][11][12][13][14] So, the present research aimed to develop a stability indicating reverse phase liquid chromatographic method for the simultaneous determination of MET, VIL and REM in bulk and drug formulation suitable for routine analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Many other analytical methods for determination of MET in pharmaceutical and biological matrices, either alone or in combination with other drugs were also reported. Recent reported methods include spectroscopy [6][7][8] , HPLC 9-11 , HPTLC [12][13][14] , LC/MS [15][16][17][18][19] , capillary electrophoresis (CE) 20&21 and voltammetry [22][23][24] . Most of these previously published methods were focusing on the determination of MET regardless its main impurity CGN.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many reports was published for regular Quality control checking of REMO combination with MET in both alone and formulation dosage forms using UPLC/PDA detection [11]. Utilization of full factorial Box-Behnken design model developed RP-HPLC and Green Second-Derivative UV Spectroscopic Method [12,13]. For Greenness Evaluation established Eco-friendly manipulated UV spectroscopic techniques, semi-quantitative and quantitative methods and the employments of modification of UV spectra, three smart, reproducible and non-sophisticated spectroscopic techniques were developed [14].…”
Section: Introductionmentioning
confidence: 99%